A novel HPLC-MS/MS approach for the identification of biological thiols in vegetables. (1st March 2021) - Millan, Silvia; Jeffery, David W.; Dall'Acqua, Stefano; Masi, Antonio
Highlights: A HPLC-MS/MS approach was developed to identify unknown thiols in vegetables. Specific thiol tagging with DTDP was used to screen for and identify thiols. Identified compounds were confirmed by HRMS and analysis of authentic standards. 1-β-Thio-d -glucose was identified in Brassica for the first time. Abstract: Thiols are important natural molecules with diverse functions, ranging from acting as antioxidants that prevent chronic diseases to contributing aromas to foods and beverages. Biological thiols such as glutathione are of particular interest due to their functional roles, which include helping maintain cellular redox homeostasis and detoxifying reactive oxygen species. However, knowledge of thiol metabolism in plants is limited to studying known compounds, whereas other important thiol-containing metabolites could also exist. This work aimed to develop a new analytical approach for screening of thiols in plants, using four vegetal examples and beginning with HPLC-MS/MS in precursor ion scan mode, after extraction and thiol-specific derivatisation with 4, 4′-dithiodipyridine (DTDP). Compound identity for prospective thiols was then proposed using HPLC with high resolution MS, and verified with authentic standards. This approach could lead to prospecting studies that identify thiols with potential roles in metabolic pathways, nutritional value of vegetables, or flavouring of foods.